Kontribusi Pertanian Berbasis Pemanfaatan Lahan Pekarangan Terhadap Ketahanan Pangan Rumah Tangga di Kabupaten Malang Jawa Timur - Jihad, Fajri Dhaniar Mohammad; Riana, Fitria Dina; Toiba, Hery; Pariasa, Imaniar Ilmi (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
Food security is a condition in which food is fulfilled at the individual level. One of the activities that has contributed to food security and can be carried out by the community at the household level in Malang Regency is by utilizing land in the yard to be used as agricultural land. Food security that is guaranteed at the national or regional level does not always reflect food security at the household level. Therefore, it is necessary to measure the level of food security at the household level separately. This study was conducted with the aim of analyzing the level of household food security of the farmers of yard-based agricultural activities and the contribution of yard-based agricultural activities to household sector food security in Malang Regency. The analysis method used in this study is the Jonsson and Toole indicator to measure the level of household food security. The variables used to measure the level of food security are adult equivalent calorie uptake (TKE) and food expenditure share (PPP). The  research results showed that the level of food security of the farmers of yard-based agricultural activities in Malang Regency was 53.57% under food security conditions. In addition, the yard-based agricultural activities carried out by the community have contributed to food security by 1,620,922.60 kcal (13.66%) to the accumulated household calorie uptake of the farmers of yard-based land utilization activities in Malang Regency, 37.98% to reducing the cost of shopping for household food needs, and IDR 362,531 to additional household income.